PRATYAKSA: KONSEP PEMBELAJARAN HERMENEUTIS BAGI SISWA DALAM KEHIDUPAN SOSIO-KULTURAL DI BALI - W.A. Sindhu Gitananda; I Made Yudabakti (UNHI PRESS, 2019)
The education system should be a common thread between socio-cultural natural life and new generations of Bali. In this connection a learning concept is needed that brings those individuals closer to socio-cultural natural experiences. In the Tattwa texts it is explained that the first in an effort to obtain true knowledge is the concept of ‘pratyakṣa’. Through pratyakṣa, the students are invited to always be directly connected in a process of experiencing hermeneutically with the socio-cultural life of Bali. Thus the tradition and new generation of Bali go hand in hand in a hermeneutical situation of understanding each other.